Unital positive Schur multipliers on $S_n^p$ with a completely isometric dilation - Duquet, Charles (MATHEMATICA SCANDINAVICA, 2024)
Let $1<p eq 2<∞ $ and let $S^p_n$ be the associated Schatten von Neumann class over $n× n$ matrices. We prove new characterizations of unital positive Schur multipliers $S^p_n→ S^p_n$ which can be dilated into an invertible complete isometry acting on a non-commutative $L^p$-space. Then we investigate the infinite dimensional case.